POSSIBILITIES OF MARINE FISH CULTURE IN THE SALT-PAN AREAS AT TUTICORIN - Nair, R V; Bensam, P; Marichamy, R (Indian Journal of Fisheries, 2011)
The paper gives an account of the environmental conditions and the aquatic biota in the salt-pan areas at Veppalodai, north of Tuticorin. Cultivable fishes such as Chanos chanos, Mugil cephalus, the crab, Scylla serrata and the prawn, Penaeus indicus have been observed to thrive well. A seasonal fishery for C. chanos with an average annual yield of 4,000 kg is existing at present under conditions, when no controls are exercised for the normal growth and survival of the naturally recruited stock which is open to the attack of predatory birds, crabs and snakes. It is felt that the possibilities of culturing such species as C. chanos are good under controlled conditions and safety from predators